Biodiversity conservation and management through forest landscape restoration in the Western Himalaya, India - Negi, Vikram S.; Pathak, Ravi; Dangwal, Bhawna; Joshi, Ravindra K.; Airi, Subodh; Sekar, K. C.; Pant, Shreekar; Bhatt, Indra D.; Samant, S. S. (Frontiers in Conservation Science, 2025)
UN Decade on Ecosystem Restoration seeks to advance existing global commitments, including the Bonn Challenge, Aichi Biodiversity Targets, and Sustainable Development Goals (SDGs), to promote effective environmental management. In the Indian context, ecosystem restoration is vital in enhancing the well-being of nearly 700 million rural inhabitants who depend directly on land resources. Considering this, the present study evaluates three decades (1992–2024) of restoration efforts at the ‘Surya-Kunj’ model site in the central Himalaya. Restoration of the degraded land began in 1992 with the plantation of 172 multipurpose plant species, followed by gap-filling activities until 2014. The adoption of simple bioengineering techniques and interventions facilitated the restoration process. Among the planted species, 136 native Himalayan species showed better performance, with a success rate of 62% compared to 38% of non-native species; the overall survival rate was 52% in the restoration model. Most planted tree species are now naturally regenerating, with healthy populations of seedlings and saplings. The success of the restoration model is evident from the rich biodiversity now present at the site, including 100 medicinal plant species, >160 species of birds, >100 species of butterflies, 86 bryophyte species, and >30 species of lichens. Community participation has been a key focus, fostering local stewardship, sustainable resource use, and replicating restoration practices on private lands. The site is also a knowledge dissemination hub for school students, teachers, and the local community. To date, we have conducted about 62 conservation education workshops, engaging over 5331 stakeholders and students, and building their capacity on restoration and diverse conservation issues in the Himalaya. The ‘Surya-Kunj’ model demonstrates that integrating ecological principles with community involvement can yield a self-sustaining, biodiversity-rich site, offering a replicable framework for Himalayan landscape restoration.